Clinical Diagnostic Criteria Have a High Impact on the Frequency of Dementia in Late-Stage Parkinson's Disease - Severiano e Sousa, Catarina; Fabbri, Margherita; Godinho, Catarina; Simões, Rita; Chendo, Inês; Coelho, Miguel; Martins, Isabel Pavão; Ferreira, Joaquim J. (Frontiers in Neurology, 2021)
Background: Cognitive impairment is a potential late feature of Parkinson's disease (PD). However, studies in patients with late-stage PD are lacking due to the particular characteristics of this population. Objectives: To evaluate the frequency of dementia in late-stage PD patients and to assess the impact of using different diagnostic criteria. Methods: We conducted a cross-sectional study to estimate the frequency of dementia in late-stage PD patients using the International Parkinson and Movement Disorders Society (MDS) (Level II) clinical diagnostic criteria as the primary outcome. We also applied other diagnostic criteria (MDS (Level I), DSM-IV, and DSM-5 criteria) to determine their applicability and impact on dementia frequency. Results: 93 participants with a mean age of 75.8 years (SD 6.8) and 16.5 years (SD 7.5) of disease duration were included. 64.3% were classified as demented using the International Parkinson and Movement Disorders Society (MDS) (Level II) clinical diagnostic criteria. We observed a high discrepancy on the frequency of dementia depending on the criteria applied ( 6.2% with MDS (Level I), 58.8% with DSM-IV, and 72.0% with DSM-5 criteria). Conclusions: We found a frequency of dementia below what was observed in similar populations. The particular characteristics of our sample may have contributed as protective factors for late-stage dementia. Dementia frequency varied depending on the criteria used mainly due to the presence of major depression.